2015
DOI: 10.1515/physio-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

Review of research on the impact of physical activity on mental state of the elderly

Abstract: The aim of the review was to find the factors correlated to the state of mental and physical health of the elderly as well as the factors, behaviours and activities that can be influenced and potentially modified. We performed an analysis of results of research conducted in many places all across the world among the persons after the age of 50. The results of this research indicate a significant role of physical activity in functioning of the elderly. They show how it influences their performance of everyday a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…It is worth emphasizing that the results clearly indicate positive correlations between physical activity and good psychological attitude among both men and women. Based on the current research, as well as studies by other authors, it is possible to state that it is worthwhile encouraging individuals with decreased mood to engage in various forms of physical recreation, and it is possible to treat physical activity as a method of prevention against decreased mood, depression and the consequences of such states [104,105]. Thanks to the correlation analyses, it was also observed that masculinity is positively correlated with psychological attitude in each of the studied groups.…”
Section: Discussionmentioning
confidence: 60%
“…It is worth emphasizing that the results clearly indicate positive correlations between physical activity and good psychological attitude among both men and women. Based on the current research, as well as studies by other authors, it is possible to state that it is worthwhile encouraging individuals with decreased mood to engage in various forms of physical recreation, and it is possible to treat physical activity as a method of prevention against decreased mood, depression and the consequences of such states [104,105]. Thanks to the correlation analyses, it was also observed that masculinity is positively correlated with psychological attitude in each of the studied groups.…”
Section: Discussionmentioning
confidence: 60%
“…Exercise could induce more dopamine secretion to help the aged maintain good mentality, expand the scope of social activities, enrich their mental world, and reduce the incidence of chronic diseases (Du et al, 2019). Morga et al (2015) have reported that physical exercise plays an important role in keeping the physical function of the aged, and it can affect their daily activities, mood and mental health. Ewing et al (2017) also have reported that poor sleep quality is a common early manifestation of mental disorders.…”
Section: Correlation Between Mental Health Score and Bmd In Older Womenmentioning
confidence: 99%
“…21,22 A review of research on the impact of physical activity on mental and somatic status of elderly adults has indicated that the physical activity can be an alternative to pharmacological therapy for depressive disorders, and thus, it can affect the reduction of costs related to medical care for older persons. [23][24][25] Furthermore, regular physical exercises, physical therapy, and respiratory exercises cause the reduction of depressive symptoms, mental disorders, and anxiety states. 25 Moreover, the improvement occurs also in the area of social functioning, somatic conditions, and physical performance, as well as cognitive functions, attention span, and memory.…”
Section: Anxiety and Depressionmentioning
confidence: 99%